حالات تعليق علاقة العمل - - حريزي كمال - غانس شيماء (جامعة المسيلة, 2022)
لطالما كانت الدولة تسعى إلى الرقي والتطور في جميع المجالات خاصة ما يتعلق بمجال مرافقها الإدارية العامة التي تلبي حاجيات مواطنيها، بواسطة أعوان عموميون وعمال أجراء، وعليه حاولنا التطرق إليه من خلال هذه الدراسة إلا أن هاذين الأخيرين يمكن أن تواجههما مشاكل وحاجيات شخصية أثناء علاقة عملهم فتدفع بهم إلى التعليق المؤقت لعلاقتهم الوظيفية أو العقدية وتحول دون سريان العقد بطريقة عادية، وهو ما دفع بالمشرع الجزائري لسن بعض الوضعيات القانونية التي تكفل للموظف العمومي حقه في التجميد المؤقت لعمله وهو ما تضمنه الأمر 06/03، وحالات تعليق علاقة العمل بالنسبة للعامل وهو ما نص عليه في مادتيه 64و65 من قانون علاقات العمل رقم11/90. إلا أن هذه الوضعيات القانونية أو حالات تعليق علاقة العمل يمكن أن تنجر عنها جملة من الآثار بالنسبة لكلا الأطراف وهو ما حاول المشرع الجزائري تنظيمه وتوضيحه من خلال النصوص القانونية والتنظيمية خاصة فيما يتعلق بالمنازعات التي تقوم بهذا الشأن. الكلمات المفتاحية: الوضعيات القانونية، حالات التعليق، حالات تعليق علاقة العمل، الموظف، العامل. Abstract: The state has always been striving for advancement and development in all fields, especially with regard to the field of its public administrative facilities that meet the needs of its citizens, by means of public agents and wage workers, and accordingly we tried to address it through this study, but these two may face personal problems and needs during their work relationship, so they pay them to the temporary suspension of their functional or contractual relationship and prevent the contract from being valid in a normal way, which prompted the Algerian legislator to enact some legal positions that guarantee the public employee the right to temporary freezing of his work, which is included in Order 06/03, and cases of suspension of the work relationship for the worker, which is stipulated It is stipulated in Articles 64 and 65 of Labor Relations Law No. 90/11. However, these legal situations or cases of suspension of the work relationship can result in a number of effects for both parties, which the Algerian legislator tried to organize and clarify through legal and regulatory texts, especially with regard to disputes in this regard. Keywords: legal situations, cases of suspension, cases of suspension of the work relationship, the employee, the worker.
Keywords: : الوضعيات القانونية، حالات التعليق، حالات تعليق علاقة العمل، الموظف، العامل.